Episodic Structure in the Ugaritic Keret-Legend: Comparative Studies in the Compositional Technique - Lichtenstein, Murray Howard
PhD Diss.; Order No. 8008748. Cf. DissAbstr 40 (1980) 5421-A.; completes 41:597.